Observation of a Te4+ center with broad red emission band and high fluorescence quantum efficiency in TeO2-Li2O glass - Costa, F. B.; Souza, A. K.R.; Langaro, A. P.; Silva, J. R.; Santos, F. A.; Figueiredo, M. S.; Yukimitu, K. [UNESP]; Moraes, J. C.S. [UNESP]; Nunes, L. A.O.; Andrade, L. H.C.; Lima, S. M. (Elsevier, 2018)
In this work, a lithium tellurite glass (80TeO2− 20Li2O, in mol%) was synthesized and its optical properties were analyzed. This glass matrix has been extensively studied, mainly due to its highly nonlinear optical properties, but there have been no reports concerning its luminescence properties. To the best of our knowledge, this is the first observation of visible emission related to Te4+ centers in a lithium tellurite glass. A broad and intense emission band was centered at 650 nm and there was a broad excitation band in the UV–Vis region. The emission lifetime at room temperature was approximately 7.0 ± 0.2 µs and the fluorescence quantum efficiency was 63 ± 6%. These characteristics indicated that the system consisting of Te4+ centers in lithium tellurite glass is a good candidate as a phosphor material for various applications.
Keywords: Fluorescence quantum efficiency; Lithium tellurite glass; Te4+ center; Thermal lens spectrometry